Capacitive and diffusion-controlled mechanism of strontium oxide based symmetric and asymmetric devices. (February 2020) - Iqbal, Muhammad Zahir; Haider, Syed Shabhi; Siddique, Saman; Karim, Muhamamd Ramzan Abdul; Zakar, Sana; Tayyab, Muhammad; Faisal, Mian Muhammad; Sulman, Muhammad; Khan, Abbas; Baghayeri, Mehdi; Kamran, Muhammad Arshad; Alherbi, Thamer; et al.
Highlights: Strontium oxide based symmetric and asymmetric devices. Analysis of Faradaic and non-Faradaic contribution in both devices. Diffusive contribution is dominant in symmetric device architecture. Capacitive contribution is prominent in asymmetric device architecture. Abstract: A systematic approach has been employed to statistically analyze the Faradaic and non-Faradaic mechanism on electrodes. Two strategies have been adopted for device design, i.e. symmetric and asymmetric, by using the metal oxide synthesized via sonochemical method and activated carbon electrode. Structural and electrochemical characterization have been performed to investigate the morphological and electrochemical properties of electrode material. Both devices are electrochemically examined by using cyclic voltammetry (CV) and Galvanostatic charge discharge (GCD) measurements to evaluate the electrochemical performance. CV curves are further explored to study the capacitive and diffusive contribution in both devices. The diffusive-controlled contribution at low scan rate in asymmetric device is about 65% which is suitable for supercapattery applications while the symmetric device shows 91% diffusive contribution presenting better performance for battery applications. The strategy unveils the high capacitive and diffusive contribution in asymmetric and symmetric devices, respectively. Results reveal that same material can be exploited for supercapattery and battery applications by implementing different device architectures. Graphical abstract: Image, graphical abstract